LIFE POTENTIAL OF REHABILITATION PEDAGOGY - Ermakov, Ivan (Mountain School of Ukrainian Carpaty, 2019)
In the article the peculiarities of development and formation of rehabilitation pedagogy on the basis of ideas of pedagogy of life creation are revealed. The author emphasizes the necessity of updating the content, technological support, defining the functions of rehabilitation pedagogy, since it reveals a new vision of the problem and promotes the prognostic philosophy of the integrated school of the century. It is pointed out that the most valuable asset of rehabilitation pedagogy is that its goals, content are not only close to the educators-reformers, but also to the children who become co-creators of new models of the 21st century schools, who are learning more about their lives to master the art of life-giving, the art of being. The article emphasizes that the important ability of a growing person to "learn to be" must be based on the ability to know oneself, to be aware of one's strengths and abilities, to try to end such phenomena as fatalism and humility, which in certain circumstances means learning to live, to know, to think, freely and critically, learn to love the world and make it more human, learn to live and create. After all, mastering by a child with a special need the art of living helps her or him to master better innovative technologies of self-rehabilitation, self-mobilization, which are vital for her or his development. The methodological guidelines of the study represent the theoretical concept of the development of rehabilitation pedagogy, which explains the phenomenon under study in the context of the activity of pedagogy of life-creation. The author focuses on the applied tasks of rehabilitation pedagogy, which consist in theoretical and organizational and practical support of educational and rehabilitation process both in the system of special education and in the process of integration of children with special needs in secondary schools. It is noted that effective integration into society, development of vital competence of children with special needs, can be successful under the condition of creation of innovative educational and rehabilitation, correction and development space, which systematically combines medical, psychological, pedagogical and social aspects.